Liss 2014 2015
DOI: 10.1007/978-3-662-43871-8_225
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Among Service Quality, Customer Satisfaction and Customer Loyalty: A Case Study of Carrefour Hypermarket

Abstract: The purpose of this study is to explore the relationship among service quality, customer satisfaction and customer loyalty for Carrefour Corporation in Taiwan. A questionnaire survey was conducted to fulfill this purpose using a sample of 290 effective questionnaires gathered from customers in five service areas of Carrefour hypermarket at Tainan branch. The analysis of statistics such as hierarchical regression analysis, path analysis and canonical correlation analysis were used to analyze the data. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Satisfaction in the virtual environment (e-satisfaction) has become a crucial factor in competing and achieving success in the market (Cox & Dale, 2001;Anderson & Srinivasan, 2003;Zeglat et al, 2016). Hsu & Hsu (2008), Shahabuddin (2014), andZeglat et al (2016) emphasize the significant relationship between service quality and customer satisfaction. It has been argued that enhancing e-service quality not only makes the service more appealing but also increases customer satisfaction (Fu Tsang et al, 2010;Bernardo et al, 2012).…”
Section: The Relationship Between Brand Image and E-trust For Online ...mentioning
confidence: 99%
“…Satisfaction in the virtual environment (e-satisfaction) has become a crucial factor in competing and achieving success in the market (Cox & Dale, 2001;Anderson & Srinivasan, 2003;Zeglat et al, 2016). Hsu & Hsu (2008), Shahabuddin (2014), andZeglat et al (2016) emphasize the significant relationship between service quality and customer satisfaction. It has been argued that enhancing e-service quality not only makes the service more appealing but also increases customer satisfaction (Fu Tsang et al, 2010;Bernardo et al, 2012).…”
Section: The Relationship Between Brand Image and E-trust For Online ...mentioning
confidence: 99%
“…These constructs have been conceptualized as being distinct but closely related. Service quality positively influences customer satisfaction (Parasuramanet al, 1988;Johnson and Fornell, 1991;Cronin and Taylor, 1992;Kristensen et al, 1999;Cronin et al, 2000;Zeithaml and Bitner, 2000;Sivadas & Baker-Prewitt, 2000;Wang et al, 2002;Kuo-YF, 2003;Beerli et al, 2004;Lee and Lin, 2005;Choi et al, 2005;Collier and Bienstock, 2006;Park & Kim, 2006;Bauer et al, 2006;Spreng and Mackoy, 1996;Al-hawari, 2008;Hsu and Hsu, 2008;Eakuru and Mat, 2008;Saha, and Theingi, 2009;Rod et al, 2009;Zhang, 2009;Yee et al, 2010;Suh and Pedersen, 2010;Saunders and Petzer, 2010;Liang & Gera, 2011). Researches in telecom industry showed that service quality positively and significantly influences customer satisfaction (Kim et al, 2004;Tung, 2004;Turel and Serenko, 2006;Kuo et al, 2009;Lee, 2010a).…”
Section: Service Quality (Sq) and Customer Satisfaction (Cs) Relation...mentioning
confidence: 99%